Mangrove Nursery Training fo Marine and Fisheries Student Group in Buton Tengah Regency - Adi Parman Rudia, La Ode; Izal; Muhamad Azwar Syah; Phradiansyah; La Ode Abdul Fajar Hasidu (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
Mangrove degradation that occurs in various regions of Southeast Sulawesi, especially in Mawasangka sub-district, Central Buton Regency, is caused by several factors, one of which is the conversion of mangroves into ponds. Real action is needed in mangrove rehabilitation efforts. Some concrete actions in mangrove rehabilitation efforts include species recognition activities as well as mangrove nurseries, which can later be used as a source of seeds for mangrove planting activities. This activity aims to provide understanding to students of the Marine Science and Fisheries Science Study Program regarding the types of mangroves, seed selection, and how to seed mangroves. The methods used in carrying out this activity were a survey of mangrove locations, introduction of mangrove species, selection of seeds, nurseries, and evaluation of activities. A mangrove location survey was carried out to inspect mangrove areas that were open due to conversion into ponds. Species introduction is carried out directly in the mangrove area around the pond. Seed selection is carried out on mangrove propagules that meet the requirements as a seed source. Mangrove seeding is carried out on previously selected mangrove species. Meanwhile, evaluations are carried out 30 days after planting, to see the level of success of mangrove seedlings in growing. The results obtained were that there were 16 types of mangroves, with 4 types of mangroves used as seed sources, namely R. apiculata, R. mucronata, C. tagal, and B. gymnorrhiza. There are a total of 1200 mangrove seedlings that have successfully grown, with a growth success rate of 100%. Apart from that, the participants' capacity in the aspect of introducing types of mangroves, how to seed several types of mangroves, and how to select good seeds has increased. Meanwhile, the participants had a very good understanding of the function and role of mangroves for the environment and society.